Charles Dickens, A Tale of Two Cities and the French Revolution
XI, 212 p. 7 illus.
Keywords: A Tale of Two Cities has always been one of Dickens's most popular texts. Using a variety of disciplinary approaches, this new collection of essays examines the origins of Dickens vision of the French Revolution, the literary power of the text itself, and its enduring place in British culture through stage and screen adaptations.